When Decisions Should Be Shared: A Study of Social Norms in Medical Decision Making Using a Factorial Survey Approach. (January 2013) - Müller-Engelmann, Meike; Donner-Banzhoff, Norbert; Keller, Heidi; Rosinger, Lydia; Sauer, Carsten; Rehfeldt, Kerstin; Krones, Tanja
Background . Shared decision making (SDM) is often advocated as an ideal for making medical decisions. Until now, however, opinions regarding which treatment situations warrant SDM have not been systematically investigated. The purpose of this study was to examine social norms regarding medical decision making, using a factorial survey design.Methods . The factorial survey applied in this study consisted of 7 situational factors (e.g., the reason for consultation), each with 2 to 3 levels (e.g., prevention and severe disease). These factors were turned into various descriptions of treatment situations. A total of 101 physicians, 115 patients, and 113 members of self-help groups participated in the study. Each participant assessed 10 vignettes using a 5-point scale to indicate who they thought should make the decision in each specific situation.Results . Most assessments across the 3 groups called for a shared decision (39%). Ordered logistic regression analysis demonstrated that, according to study participants, all 7 situational factors (reason for consultation, time frame of negative outcomes, time pressure, number of therapeutic options, side effects, scientific evidence of efficacy, and desire to participate) significantly affected how decisions regarding treatment should be made. The strongest factor was the patient's desire to participate in decision making (odds ratio = 1.84; P ≤ 0.001), followed by the reason for consultation (odds ratio = 0.69; P ≤ 0.001).Conclusions . This study reveals that there is a general desire for SDM in a variety of treatment situations. Furthermore, based on the responses of our participants, our findings also lay the framework in determining which treatment situations warrant SDM.